Morbidity and Mortality of Very Low Birth Weight Babies in a Tertiary Level NICU - Kaur, Amandeep; Thapar, Karuna; Chhabra, Gurpreet Singh; Jaslean, - (Journal of Nepal Paediatric Society, 2016)
Introduction: The WHO defines Very low birth weight babies as birth weight < 1500 grams at birth irrespective of gestational age. The primary cause of VLBW is premature birth.The commonest conditions in this group include aspiration, infections, Hyaline membrane disease. Early onset sepsis is an important cause of illness and death among infants with very low birth weights. The objectives were to study the morbidity and mortality of very low birth weight babies in teritary level NICU in Amritsar and the sociodemographic, obstetric and neonatal variables affecting survival of VLBW infants. Materials and Method: It was an observational study and conducted in NICU of SGRDIMS&R, Amritsar, over the period of 18 months (1st October 2013 to 31st March 2015). A total of 75 VLBW neonates were observed during this period and neonatal outcome was assessed. Data so obtained was statistically analysed by Microsoft SPSS, Version 17.0.Chi Square test was applied to the data. Results: Preterm VLBW babies had high incidence of morbidities. Sepsis was the major cause (77.3%) of morbidity in VLBW neonates followed by HMD (66.7%) and NNJ (65.3%) of the neonate. Sepsis along with other factors like IVH, Pneumothorax, NEC play an important role in neonatal mortality. Conclusion: The most common cause of VLBW babies was prematurity. The mortality rate among VLBW neonates was 12%. Sepsis, HMD metabolic complications like hypoglycaemia and hypocalcemia were the major contributing factors towards mortality. J Nepal Paediatr Soc 2015;35(3):257-263